Impact on traditional hydropower under a multi-energy complementary operation scheme: An illustrative case of a ‘wind–photovoltaic–cascaded hydropower plants’ system - Jidong Li; Guangjie Luo; Tingyu Li; Lu Gao; Xinlan Liang; Jian Hu; Ying Cao; Lijian Qi; Xing Liu; Miao Huo (Energy Strategy Reviews, 2023)
Establishing a wind–photovoltaic (PV)–hydro hybrid system is a new method to utilize wind and PV power, but how multi-energy complementation affects the working modes of cascaded hydropower plants (CHP) has not been fully revealed. In this study, a wind–PV–CHP system was considered as an example and a multi-objective optimal operation model was constructed considering the maximization of both the power generation and the minimum power output. Simulation and comparison results showed that (1) the regulation capability of the hydropower was mainly used for two purposes: one was to drive the early water storage (or water release reduction) of CHP to improve the overall utilization efficiency of water resources, and the other was to drive the hydropower output to cooperate with the non-regulatable wind–PV power output in order to achieve a complementary output; (2) the different minimum outputs determined the regulation capacity for complementing the wind–PV power output, which represents the degree of complementation; and (3) complementation would significantly affect the minimum output and slightly affect the average output of CHP. Overall, this study improves our understanding of wind–PV–hydro complementary operation and can serve as a reference for actual project operation.